PENERAPAN MEDIA PEMBEMBELAJARAN KOGNITIF DALAM MATERI PERSAMAAN GARIS LURUS MENGGUNAKAN VIDEO DI ERA 4.0 - Fine Siwi; Nicky Dwi Puspaningtyas (Universitas Teknokrat Indonesia, 2020)
AbstractAt this time thinking creativity is low in the world of education. To improve creative thinking patterns urgently, as educators must have ways to improve them. Learning mathematics can be done only through the medium of learning mathematics. Audio-visual media, is a type of media used in learning activities with hearing and vision in one process or activity. Messages and information that can be channeled through this media can consist of verbal and nonverbal messages that depend on the sight whether hearing. In this 4.0 era, students are required to be better able to think cognitive in learning. Fully creative thinking including in the current era is needed. However, at this time creative thinking in the world of education is low. To improve the importance of creative thinking patterns, as educators who already have a way to improve it by using learning media. Therefore the material explanation method is made using video-based media to facilitate students in understanding the material and also improve their cognitive abilities. This research can prove through video-based learning media can be an effective method in improving students' cognitive abilities. Keywords: Media, Video, Cognitive